A Randomized Trial of a Self-Administered Parenting Intervention for Infant and Toddler Insomnia. (June 2019) - Stevens, Jack; Splaingard, Deborah; Webster-Cheng, Stephanie; Rausch, Joseph; Splaingard, Mark
Self-administered treatments may overcome access barriers to evidence-based care for pediatric sleep problems. Two hundred thirty-nine families participated in a randomized controlled trial with 3 study arms: a DVD intervention condition (the Sleep Easy Solution), a Website comparison condition, and a Wait-List comparison condition. The primary outcome was trichotomous—Do you consider your child's sleep a problem? (not a problem at all, a small problem, a very serious problem). DVD was superior to Wait-List in terms of the primary outcome ( P = .03; odds ratio = 0.44; 95% confidence interval = 0.21-0.93). Similarly, regarding secondary outcomes, DVD was superior to Wait-List in terms of longer continuous sleep periods ( P = .003), more favorable perceptions of the child's overall sleep ( P = .001), and higher parental confidence in managing the child's sleep ( P = .001). Results suggest that the DVD intervention is a promising self-administered treatment for pediatric insomnia.